2014
DOI: 10.1016/j.pain.2014.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Reduced task-induced variations in the distribution of activity across back muscle regions in individuals with low back pain

Abstract: This study investigated change in the distribution of lumbar erector spinae muscle activity and pressure pain sensitivity across the low back in individuals with low back pain (LBP) and healthy controls. Surface electromyographic (EMG) signals were recorded from multiple locations over the lumbar erector spinae muscle with a 13×5 grid of electrodes from 19 people with chronic nonspecific LBP and 17 control subjects as they performed a repetitive lifting task. The EMG root mean square (RMS) was computed for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
205
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(228 citation statements)
references
References 60 publications
17
205
5
1
Order By: Relevance
“…This is line with previous studies demonstrating a non-uniform distribution of muscle activity (e.g. trapezius, lumbar erector spinae) with the possibility of activating different muscle regions depending on the task performed (Falla and Farina, 2008;Falla et al, 2014).…”
Section: Traction and Compressionsupporting
confidence: 93%
“…This is line with previous studies demonstrating a non-uniform distribution of muscle activity (e.g. trapezius, lumbar erector spinae) with the possibility of activating different muscle regions depending on the task performed (Falla and Farina, 2008;Falla et al, 2014).…”
Section: Traction and Compressionsupporting
confidence: 93%
“…Other studies specifically reported a caudal shift of back muscle activity centroid during muscle fatigue in asymptomatic participants. 5,6,22 This observation confirms that the lumbar erector spinae muscles adapt over time in the presence of muscle fatigue. These adaptations in muscle activity during sustained contractions may reflect an efficient strategy to maintain task requirements by distributing the activity across different regions of the muscle.…”
Section: Discussionsupporting
confidence: 66%
“…The centroid position is one of the commonly used variables, as the literature and recent studies reported changes in the distribution of muscle activity characterized by a migration of the centroid during a fatigue task. 2,5,6 Indeed, a caudal and lateral shift of the centroid was observed in the current study. Other studies specifically reported a caudal shift of back muscle activity centroid during muscle fatigue in asymptomatic participants.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Adopting non-uniform muscle activity recruitment may help participants develop motor strategies and facilitate adaptation to different physiological and/or mechanical perturbations of the spine. Low back muscle activity measured by high-density sEMG has also been shown to discriminate patients with chronic low back pain from healthy individuals through different motor tasks (Abboud et al, 2014; Falla et al, 2014). To our knowledge, no study has investigated muscle activity reflex variables with high-density sEMG.…”
Section: Introductionmentioning
confidence: 99%